2018
DOI: 10.1111/1755-0998.12747
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating methods to visualize patterns of genetic differentiation on a landscape

Abstract: With advances in sequencing technology, research in the field of landscape genetics can now be conducted at unprecedented spatial and genomic scales. This has been especially evident when using sequence data to visualize patterns of genetic differentiation across a landscape due to demographic history, including changes in migration. Two recent model-based visualization methods that can highlight unusual patterns of genetic differentiation across a landscape, SpaceMix and EEMS, are increasingly used. While Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Furthermore, the barrier in the northwestern corner is consistent with the lower levels of allele sharing we found between the Breton departments and the southeastern corner of France. Apart from some possible artifacts due to the presence of unsampled regions (House et al, 2018), we found the EEMS results consistent with the rest of the data collected in our study. Indeed, another group with a higher internal migration rate according to the EEMS results is represented by the north and the northeastern departments.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the barrier in the northwestern corner is consistent with the lower levels of allele sharing we found between the Breton departments and the southeastern corner of France. Apart from some possible artifacts due to the presence of unsampled regions (House et al, 2018), we found the EEMS results consistent with the rest of the data collected in our study. Indeed, another group with a higher internal migration rate according to the EEMS results is represented by the north and the northeastern departments.…”
Section: Discussionsupporting
confidence: 89%
“…Boundary‐based methods include edge detection techniques (e.g., Cercueil, François, & Manel, ; House & Hahn, ; Jombart, Devillard, & Balloux, ; Jombart, Devillard, Dufour, & Pontier, ; Monmonier, ; Piry et al., ), and Bayesian clustering algorithms (reviewed in François & Durand, ) aim to delineate discrete or admixed populations in space (Wagner & Fortin, ). They allow identifying spatial genetic boundaries that are visually (e.g., Frantz et al., ; Prunier et al., ) or statistically (e.g., Balkenhol et al., ; Jay et al., ; Murphy, Evans, Cushman, & Storfer, ) compared to landscape patterns.…”
Section: How To Infer the Environmental And Individual Effects On Nonmentioning
confidence: 99%
“…Although intuitive, there are only a few such programs available and all of them were published very recently. Un‐PC (House & Hahn, ) is an r package that projects principal components analysis (PCA)‐based genetic distances of pairs of populations (the “ un‐PC ” values) as ellipses to highlight areas of extreme genetic differentiation and similarity, and therefore areas of high and low resistance. Un‐PC is model‐free in the sense that it does not specify a particular mechanistic model underlying the observed genetic pattern.…”
Section: Introductionmentioning
confidence: 99%
“…However, mapi directly projects ellipses representing genetic distances between pairs of individuals, which ignores population‐level correlations between genetic distance and environmental features. Moreover, mapi is implemented in the open source database postgresql (Momjian, ), which requires relatively complicated database installation and configuration (House & Hahn, ). In contrast, a third program, DResD , is presented in the form of an r script and calculates resistance using population‐level information (Keis et al, ).…”
Section: Introductionmentioning
confidence: 99%